The social income of the Irish Free State, 1926-38 - Duncan, G. A. (Statistical and Social Inquiry Society of Ireland, 1940)
In the Economic Journal of March, 1933, Dr. T. J. Kiernan published an estimate of the national income of the Irish Free State for the year 1926, and followed it up with a paper, read before this Society in June, 1933, on the distribution of national expenditure in the same year. The Commission of Inquiry into Banking, Currency and Credit found that it required an estimate relating to some more recent date, and also, if possible, some indication of the changes consequent upon our economic convulsions of 1931-34. Dr. Kiernan's estimate and mine, arrived at independently by the use of completely different methods, congrued very closely, which affords us some ground for hoping that they both lie reasonably near the truth. This paper constitutes a revision and extension. I will present the broad results relating to the different main components of the social income and their changes between 1926 and 1938.
Read on Thursday, 26th October, 1939
Keywords: National income; Social income; 314.15